2004
DOI: 10.1021/jp036996s
|View full text |Cite
|
Sign up to set email alerts
|

Distance-Dependent Electronic Coupling at Molecule−Metal Interfaces:  C60/Cu(111)

Abstract: We probe electronic interaction at molecular-solid/metal interfaces in the model system of C60/Cu(111) using femtosecond two-photon photoemission (2PPE) spectroscopy. The second lowest unoccupied molecular orbital (LUMO+1) and the LUMO+2 levels in C60 are transiently populated via the creation of electronic excitons, with lifetimes in the 10-14−10-13 s region, likely due to self-trapping and/or decay into lower-lying exciton states. These lifetimes decrease as film thickness decreases. The effect is seen for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 40 publications
3
61
0
Order By: Relevance
“…They determined the lifetime of the LUMO+1 to be 300 ps for a film of 20 nm thickness, 268 ps for 10 nm, 107 fs for 3 nm and 60 fs for 1 nm. Dutton and Zhu [41] showed that the lifetimes of excitations involving the LUMO+2 and LUMO+1 exhibits an exponential dependence on film thickness which is in agreement with charge diffusion into the copper substrate.…”
Section: Thin Films On Cu(111)mentioning
confidence: 59%
See 1 more Smart Citation
“…They determined the lifetime of the LUMO+1 to be 300 ps for a film of 20 nm thickness, 268 ps for 10 nm, 107 fs for 3 nm and 60 fs for 1 nm. Dutton and Zhu [41] showed that the lifetimes of excitations involving the LUMO+2 and LUMO+1 exhibits an exponential dependence on film thickness which is in agreement with charge diffusion into the copper substrate.…”
Section: Thin Films On Cu(111)mentioning
confidence: 59%
“…As already mentioned in 1.1.3 in fullerite the absorption of a photon most of the time does not generate free charge carriers and other effects obscure the conduction band gap in 2PPE, EELS, or AS [41]. As pointed out by Sawatzky and coworkers [83] and Kabler and coworkers [40] the conduction band gap is given by the onset of the PE spectra and the IPE spectra, because the conduction electrons and holes have energies as close as possible to the band gap.…”
Section: Electrostatic Effectsmentioning
confidence: 95%
“…Dutton et al [14] measured the dispersions and lifetimes of C 60 molecular states and substrate-derived IPS, with corroboration by Shipman et al [15]. Additionally, Shipman et al used calculations of orbital orientations with respect to nearest neighbor C 60 molecules to predict effective masses of molecular states.…”
Section: Two-photon Photoemissionmentioning
confidence: 76%
“…Figure 2a shows the morphology after deposition of ∼0.08 ML of C 60 molecules onto the grid surface at RT. As expected, the fullerenes tended to selectively adsorb on the clean Cu regions due to the relatively stronger interaction between C 60 and Cu, [19][20][21][22] at which charge transfer from substrate to C 60 is reported and chemical bonding is assigned. No nucleation was observed for C 60 at the c(2 × 2) surface.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of C 60 on metal 7,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] or semiconductor surfaces 23, [38][39][40][41][42][43][44] has been studied extensively using a variety of experimental techniques. Charge transfer occurs commonly at C 60 -metal interfaces, affecting the geometrical and electronic properties of the overlayers.…”
Section: Introductionmentioning
confidence: 99%